A Secured Model of E-Tendering Using Unified Modeling Language Approach - Mohd Haslina; Baharom Fauziah; Muhd Darus Norida; Saip Mohamed Ali; Marzuki Zaharin (International Journal of Supply Chain Management, 2017)
E-Tendering systems remain uncertain on issues relating to legal and security compliance, in which unclear security framework is one of the issues. In te current situation, tendering systems are lacking in addressing integrity, confidentiality, authentication, and non-repudiation. Thus, ensuring the system requirements, consider security and trust issues has to be regarded as one of the challenges in developing an e-Tendering system. Therefore, this paper a model of a secured e-Tendering system using Unified Modeling Language (UML) approach. The modelling process begins with identifying the e-Tendering process, which is based on Australian Standard Code of Tendering (AS 4120-1994). It is followed by identifying the security threats and its countermeasure. The use case approach has been proven reliable in determining appropriate requirements for handling security issues. Having considered that, the outcome of this paper is a secured e-Tendering model. The model can guide developers as well as other researchers.